3
$\begingroup$

In Bill Casselman's notes on root systems (http://www.math.ubc.ca/~cass/courses/tata-07a/Roots.pdf), I am confused about the proof of the result $s_{\alpha}(\beta)^{\vee} = s_{\alpha^{\vee}}(\beta^{\vee})$ for any roots $\alpha,\beta$ (Corollary 3.10).

In these notes a root system is a quadruple $(V,\Sigma, V^{\vee}, \Sigma^{\vee})$, where $V, V^{\vee}$ are finite dimensional real vector spaces in a perfect pairing, and $\Sigma \subseteq V - 0, \Sigma^{\vee} \subseteq V^{\vee} - 0$ are finite subsets in bijection $\beta \mapsto \beta^{\vee}$. The usual axioms for the root system are given, except we do not require that $\Sigma$ spans $V$.

It is claimed that the result $s_{\alpha}(\beta)^{\vee} = s_{\alpha^{\vee}}(\beta^{\vee})$ can be proved in two ways: from Corollary 3.9, and from the orthogonal reflection formula (Corollary 3.3).

I can't see how this follows from Corollary 3.3, nor why Corollary 3.9 is true.

Method 1: Using Corollary 3.9, which states that the coroot $\alpha^{\vee}$ of a root $\alpha$ is the unique element of $V^{\vee}$ which lies in the span of $\Sigma^{\vee}$, satisfies $\langle \alpha, \alpha^{\vee} \rangle = 2$, and satisfies $$\sum\limits_{\gamma \in (\beta + \mathbb{Z}\alpha) \cap \Sigma} \langle \gamma, \alpha^{\vee} \rangle = 0 $$

for all roots $\beta$. It is claimed that if $l$ is another element of $V^{\vee}$ satisfying these properties, then $l - \alpha^{\vee}$ must be zero, but I don't see why this is.

Method 2: For $v, w \in V$, define

$$v \bullet w = \sum\limits_{\gamma \in \Sigma} \langle v, \gamma^{\vee} \rangle \langle w, \gamma^{\vee} \rangle$$

Then Corollary 3.3 says that for any $v \in V$ and any root $\beta$,

$$\langle v, \beta^{\vee} \rangle = 2 \frac{v \bullet \beta}{\beta \bullet \beta}$$

I don't see why Corollary 3.3 implies that $s_{\alpha^{\vee}}(\beta^{\vee}) = s_{\alpha}(\beta)^{\vee}$.

$\endgroup$
1
  • 6
    $\begingroup$ Method 1: Bourbaki Lie Groups and Lie Algebras Ch. VI section 1.1, Lemma 2 and equations (5), (6), and (7) near the end of that section (using that the reflections preserve the chosen inner product by design). Method 2: If you know the result in the reduced case then use that the set of non-divisible roots always forms a reduced root system (use Prop. 13(i) in Ch. VI section 1.4 of Bourbaki, after reading section 1.2). Method 3: Lemma 3.2.4 in the book Pseudo-reductive Groups (2nd ed.), proved there for root data. General advice: read Ch. IV--VI of Bourbaki. It is awesome. $\endgroup$
    – nfdc23
    Jan 25, 2017 at 3:50

1 Answer 1

2
$\begingroup$

Proof of uniqueness in Method 1: it suffices to show that $\langle \beta, l - \alpha^{\vee} \rangle = 0$ for all roots $\beta$. Write

$$(\beta + \alpha\mathbb{Z}) \cap \Sigma = \{ \beta + n_i \alpha, i = 1, ... , r \}$$

this is nonempty.

Then

$$0 = \sum\limits_{i=1}^r \langle \beta + n_i \alpha, l \rangle = r \langle \beta, l \rangle + 2(n_1 + \cdots + n_r)$$

And also

$$0 = \sum\limits_{i=1}^r \langle \beta + n_i \alpha, \alpha^{\vee}\rangle = r \langle \beta, \alpha^{\vee} \rangle + 2(n_1 + \cdots + n_r)$$

so $\langle \beta, l \rangle = \langle \beta , \alpha^{\vee} \rangle$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.